PROFILING OF A HIGH-FUNCTIONING ASD BOY: A FOCUS ON LANGUAGE ABILITIES - Nurbaizura Baharom; Yusniza Mohd Yusoff; Mazura Jamalai@Jamali (Journal of Islamic, Social, Economics and Development, 2023)
Autism Spectrum Disorder (ASD) is a condition in which individuals may display a degree of deficiency which varies widely. Those at the less severe end of the spectrum are commonly referred to as having high-functioning autism (HFA) with cognitive abilities ranging from average to above-average intelligence and good command of language. This paper focuses on a case study which aims to represent the characteristics of an HFA Malay boy with a focus on his language abilities. This is a small section of a bigger case study which investigated three Malay HFA children on their English language performances. During the data collection stage, spontaneous speech interactions in English were conducted with the child. The profiling of this Malay boy, which was included in the researchers’ previous article in 2019 with the source of interview from the father, and in an earlier article in 2018; however, was quite short. This paper describes in detail his language features that qualify him to be in this category. This is a unique case with uncommon instance of a Malaysian-born, Malaysian-raised boy acquiring L1 English with a foreign accent. The sources of the description came from interviews with the father and his two English teachers. It hopes to contribute to an increase of autism awareness and acceptance among these children’s parents, caregivers, teachers, and peers, as well as the Malaysian society at large so that more support and encouragement may be provided.